CORRELATION BETWEEN THE LEVEL OF STRESS RESISTANCE AND PROGESTERONE CONCENTRATION IN A HEALTHY WOMEN'S BLOOD IN THE LUTEAL PHASE OF THE MENSTRUAL CYCLE - V. V. Yeremenko; E. G. Potyagailo; V. G. Abushkevich; V. M. Bondina; A. P. Storozhuk (Кубанский научный медицинский вестник, 2016)
The purpose of this work is to identify the relationship between concentration of progesterone in blood and stress healthy women. Material and methods. 52 healthy women aged 18 - 45 years were observed during the luteal phases of the menstrual cycle, undergoing examination in clinic “Yekaterininskaya”, in which ones progesterone was determined by immunochemiluminescent analysis of venous blood. Regulatory-adaptive status of the subjects was assessed by parameters of the sample cardiorespiratory synchronism before and after the stressor tests “Arithmetic account”. The level of stress resistance all observed the women were divided into three groups. In the high level of stress resistance - in the blood progesterone 7.0 - 21.0 ng / mL, with a moderate - 4.0 - 6.8 ng / ml and low - 1.7 ng - 3,8 / mL Conclusion. These data indicate that between kontsenentratsiey progesterone in the blood of healthy women and stress there is a connection: the more normative importance of progesterone in the blood, the higher the level of stress.